THE ANALYSIS OF THE EXPORT OF SELECTED ITEMS OF FOUNDRY AND METALLURGICAL PRODUCTS FROM BELARUS, RUSSIA AND UKRAINE TO THE EUROPEAN UNION - Yu. A. Nikolaychik; V. E. Sobolev (Литьë и металлургия, 2017)
The EU is one of the main trade partners of Belarus, Russia and Ukraine. The export operations between these countries and EU of foundry and metallurgical products according to Harmonized Commodity Description (Group 72 «Iron and Steel») in 2009–2016 are analyzed. Information is based on official statistics of the European Union. The information about the three biggest export countries to EU on every of the abovementioned positions of Harmonized Commodity Description (HCD) is shown. Analysis of trends and variations of export from Belarus, Russia and Ukraine and some conclusions are given in the article.